Evaluation of the U.S. Adherence Questionnaires VERITAS-PRO and VERITAS-PRN for Use in Patients with Hemophilia in the German Healthcare System - von Mackensen, Sylvia; Douma, Yves; Halimeh, Susan (Hämostaseologie, 2020)
Aim Since the U.S. adherence instruments VERITAS-PRO and VERITAS-PRN were developed in another healthcare system, we assumed that they are not appropriate for the German solidarity healthcare system. This study aims to evaluate the relevance of these instruments for the German healthcare system both by people with hemophilia (PWH) and by healthcare professionals (HCP).Methods A total of 50 PWH (23 adult hemophilia patients and 27 parents of children with hemophilia) and 25 HCP rated the relevance of the single items of the VERITAS-PRO and VERITAS-PRN on a 5-point Likert scale. In addition, both groups were asked to make suggestions for additional adherence questions. To investigate the relevance of these instruments, the accordance between the raters' evaluations was determined calculating the content validity index (CVI) and the content validity ratio (CVR) based on the critical values of the CVR (CVRcritical) to exclude chance and subjectivity.Results CVI (CVR) calculations revealed three (5) “very important” items for PWH and six (11) items for HCP. Only two (3) “very important” items were evaluated by both groups. Four domains were considered not important by both groups. Six PWH made 14 suggestions and 14 HCP made 24 suggestions for additional adherence questions.Conclusion VERITAS-PRO and VERITAS-PRN have only very limited benefits for the German healthcare system. Since nonadherence has a great impact on the morbidity of PWH and on the costs for the healthcare system, there is a need for adherence instruments that are adapted to the specific needs of PWH in the German healthcare system.
Keywords: hemophilia; adherence; assessment; VERITAS-PRO; VERITAS-PRN